Lichen planopilaris induced by infliximab: A case report. (January 2020) - McPhie, Meghan L; Wang, Ami; Molin, Sonja; Herzinger, Thomas
Infliximab is a tumor necrosis factor-alpha inhibitor used to treat a range of inflammatory diseases. Most reports of cutaneous eruptions from tumor necrosis factor-alpha inhibitors have described the paradoxical development of psoriasis or psoriasiform drug reaction. In our report, we present a 31-year-old female with inflammatory bowel disease who developed an unusual lichenoid drug reaction to infliximab involving the hair follicles, resulting in progressive global alopecia. Clinical features and histopathological findings were consistent with drug-induced lichen planopilaris with eosinophils and lichenoid dermatitis.